PENINGKATAN PEMAHAMAN DAN IMPLEMENTASI BAHASA NASIONAL DAN INTERNASIONAL BAKU BAGI GURU PAUD DAN SD DI KECAMATAN GETASAN KABUPATEN SEMARANG - Henny D. Koeswanti; Mozes Kurniawan; Eunice W. Setyaningtyas; Elvira H. Radia (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2020)
The Childhood Education (PAUD) and Elementary School (SD) teachers should have adequate skills and knowledge in teaching, instilling, and being an example or role model for their students. Therefore, it was necessary to increase professionalism in terms of the use of national languages as well as international languages which are needed today, so that Indonesian students can use standard Indonesian properly and correctly.Based on the conditions encountered, the community service team at the Teaching and Education Faculty (FKIP), Satya Wacana Christian University (SWCU) Salatiga carried out community service activities with the aim of opening paradigms and training early-level early childhood and elementary school teachers to have a complete understanding of the concept of standard national and international languages and have the opportunity to improve language competence, especially English. This activity was carried out in the form of training, debriefing, and teaching simulations by four FKIP, UKSW lecturers who have Indonesian, English and educational management backgrounds.The results of the implementation of this activity could be seen at the beginning of understanding of classroom language and obtaining references to the use of standard language in the classroom to be used as capital to apply the Indonesian and English concepts.